Soil hydrology and hydric soil indicators of the Bokong wetlands in Lesotho - Mapeshoane, Botle Esther (University of the Free State, 2013)
Wetland hydrology controls the function of the wetland ecosystem and hence it is the principal parameter for delineation and management of wetlands. It is defined as the water table depth, duration, and frequency required for an area to develop anaerobic conditions in the upper part of the soil profile leading to the formation of iron and manganese based soil features called redoximorphic features. The redoximorphic features must occur at specific depths in the soil profile with specific thickness and abundance to qualify for a hydric soil indicators. Therefore, hydric soil indicators are used to evaluate the wetland hydrology if such a relationship has been verified. The aims of the study were i) to determine soil variation and hydric soils indicators along a toposequence, ii) to determine the relationships between soil water saturation, redox potential and hydric soil morphological properties and iii) to determine the distribution of soil properties and accumulation of soil organic carbon in hydric and non-hydric soils. The study was conducted at the upper head-water catchment of the Bokong wetlands in the Maloti/Drakensberg Mountains, Lesotho. The soil temperature ranged between -10 and 23°C. The soils had a melanic A overlying an unspecified material with or without signs of wetness, or a G horizon. The organic O occurred in small area. Soil profiles were dug along a toposequence and described to the depth of 1000 mm or shallower if bedrock was encountered. Redoximorphic features were described using standard soil survey abundance categories. Soil samples were collected from each horizon and analysed for selected physical and chemical soil properties. The soils had low bulk density ranging from 0.26 in the topsoil to 1.1 Mg m-3 in the subsoil. Significantly low bulk density was observed in the valleys and highest bulk densities were observed on the summits. The soil organic carbon content ranged between 0.18% in the subsoil and 14.9% in the topsoil. The soil also had a high dithionite extractable Fe (mean 93±53 g kg-1) and low CEC (mean 26±9 cmolc kg-1). Soil pH and CEC were relatively lower in the valleys and higher on the summits. Principal component analysis indicated four principal components accounted for 60% of the total variance. The first principal component that contributed 23% of the variation showed high coefficients for soil properties related to organic matter turnover, the second components were related to inherent fertility, the third and fourth were related to acidity and textural variation. Hydric indicators identified in Bokong were histisols (A1), histic epipedon (A2), thick dark surfaces (A12), redox dark surfaces (F6), depleted dark surfaces (F7), redox depressions (F8), loamy gleyed matrix (F2) and umbric surfaces (F13). The thick dark surfaces with many prominent depletions and gley matrix (A12 and F7) occurred in the valleys, while the midslopes and footslopes were dominated by umbric surfaces (A13). The indicators F6, F7 and F8 were not common. Indicators that were related to the peat formation (A1, A2 and F13) were frequently observed. The relationship between soil water saturation and redoximorphic features was verified by monitoring the groundwater table with piezometers, installed in ten representative wetlands at depths of 50, 250, 500, 750, and 1000 mm for two years from September 2009 to August 2011. Redoximorphic feature abundance categories were converted into indices. Strong correlations were observed between redoximorphic indices and cumulative saturation percentage. The depth to chroma 3 and 4 (d_34) and depth to the gley matrix (d_gley) correlations were R2 = 0.77 and R2 = 74 respectively. All redoximorphic indices were poorly correlated with average seasonal high water table. Strong correlation were also observed between profile darkening index (PDI) and cumulative saturation (R² = 0.88) and weak correlations were observed between PDI and average seasonal high water table (R² = 0.63). A paired t test indicated that soil pH, exchangeable Mg and Na, dithionite extractable Fe and Al were significantly different between hydric and non-hydric soils. Hydric soils had significantly higher Mg, Na and Fe content, and significantly low soil pH and Al content. Generally it appeared that soluble phosphorus, Fe and exchangeable bases accumulated in hydric soils, while the soil pH and Al content decreased. The mean soil organic carbon contents were 3.61% in hydric soils and 3.38% in non-hydric soils. However, non-hydric soil relatively stored more organic carbon (174.4 Mg C ha-1) than hydric soils (155.1 Mg C ha-1). The mean soil organic carbon density of the study area was 166±78.3 Mg C ha-1) and the estimated carbon stored was 21619 Mg C (0.022 Tg C; 1Tg = 1012g) within the 1000 mm soil depth. About 384.9 Mg C was stored in the hydric soils within the study area, which was about 1.9% of the total carbon stored in the area to the bedrok or depth of 1000 mm. Among the wetland types, bogs had significantly higher organic carbon levels (6.17%) and stored significantly higher carbon (179 Mg C ha-1) with at least 44% was store in the A1 horizon. It was concluded that the strong correlation observed between PDI, d_34, d_gley and cumulative saturation representing hydric indicators such as histisols (A1), histic epipedon (A2), umbric surfaces (F13), loamy gleyed matrix (F2) can be used to determine the duration and frequency of the water table in the landscape studied. These hydric indicators can be used to delineate wetlands, however, more indicators can be developed.
Thesis (Ph.D. (Soil, Crop and Climate Sciences))--University of the Free State, 2013
Keywords: Limnology; Hydromorphic soils; Hydromorphic soils -- Lesotho